The Dispersion Algorithm: Consideration of Bathymetry in 2D Mesh generation in Ocean Modeling - Feizi Chekab, Mohammad A.; Ghadimi, Parviz; Ghassemi, Hassan (International Journal of Advanced Geosciences, 2013)
The Dispersion Algorithm has been further developed and improved to control locally the distribution of nodes in the computational domain. This improvement allows the user to take into consideration the effect of the bathymetry and other physical factors while maintaining the previous global capability of the original Dispersion Algorithm. It has been demonstrated that, by a simple adjustment of the value of the key parameter r(n) resulting in a new parameter R(n, x, y), any physical factor could be taken into account for the application of the proposed Algorithm in different fields of engineering. This concept has been explored to particularly include the bathymetry of the geometrical domain as an important physical factor in ocean modeling. The applicability and efficiency of the proposed algorithm has been demonstrated using various actual geometries. The bathymetry of the Persian Gulf, the Caspian Sea and the Gulf of Mexico have been successfully modeled, analyzed, and meshed by the algorithm.